2018
DOI: 10.1002/cche.10113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bran hydration and autoclaving on processing quality of Chinese steamed bread and noodles produced from whole grain wheat flour

Abstract: Background and objectives: Consumption of Chinese steamed bread (CSB) and noodles made from whole grain wheat flour (WWF) is encouraged due to their important nutritional elements in the outer seed layers that benefit human health.However, the use of WWF is limited because of the poor processing quality and less attractive product properties of dark color, rough texture and coarse crumb structure. Three Chinese wheat cultivars, Zhongmai 895, Yumai 49, and Zhoumai 27, were used to investigate the potentials of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Wetting Lai et al (1989a) Improved bread specific volume (wetting corse bran) Lai et al (1989b) Improved bread specific volume (wetting shorts) Zhang et al (2019) Improved farinograph stability, structure, and imfinal evaluation of steamed breads. However, excesive wetting can have and slightly negative effect.…”
Section: Influence Of Bran Particle Size In Whole-grain Breadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wetting Lai et al (1989a) Improved bread specific volume (wetting corse bran) Lai et al (1989b) Improved bread specific volume (wetting shorts) Zhang et al (2019) Improved farinograph stability, structure, and imfinal evaluation of steamed breads. However, excesive wetting can have and slightly negative effect.…”
Section: Influence Of Bran Particle Size In Whole-grain Breadsmentioning
confidence: 99%
“…These observations agree with the fact that both coarse bran (Lai, Hoseney, & Davis, 1989a) and shorts (Lai, Hoseney, & Davis, 1989b), when presoaked before incorporation into the kneading process, improve the final volume of the breads. However, if this prehydration is excessive, either because of time (Chen, Rubenthaler, Leung, & Baranowski, 1988) or because of the amount of water incorporated (Zhang et al, 2019), the positive effects of presoaking can be minimized or even become slightly negative. Another pretreatment of the bran that has been studied is a preheat treatment, both dry and wet, to improve the quality of the resulting breads.…”
Section: Pretreatments Of Branmentioning
confidence: 99%
See 1 more Smart Citation
“…Using WWF to replace refined flour is not always simple. Whole wheat flour comprised of coarse bran produced CSB with better texture and crumb structure and equivalent specific volume, skin color, smoothness, and shape compared to a fine bran WWF [14]. Xu et al [12] reported that decreasing WWF particle size decreased specific volume and resulted in firmer crumbs for both STSB and NTSB.…”
Section: Introductionmentioning
confidence: 99%
“…As multifunctional food ingredients, grain flours can be used for cooking soup, noodles, steamed bread, pancake, and other foods (Chen et al, ; Zhang, Gao, & He, ). Compared with wheat flour, nowadays the coarse grain flours including millet, corn, and soybean are more popular as beneficial supplements to human health (Taghdir et al, ; Zhu, Chen, Wu, Xing, & Yuan, ).…”
Section: Introductionmentioning
confidence: 99%